The Innovation of Criminal Law Interpretation Model in Indonesia through Rule of Lenity Approach - Susilo, Erwin; Negara, Dharma Setiawan; Lufsiana, Lufsiana (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This research aims to explore and develop an innovative concept of criminal law interpretation in Indonesia through the Rule of Lenity (RoL) approach. The RoL principle, originating from the common law system, emphasizes that ambiguous criminal provisions must be interpreted narrowly and always in favor of the defendant. Within Indonesia’s civil law system, adopting RoL has the potential to strengthen legal certainty, safeguard defendants’ human rights, and reduce the risk of arbitrariness in law enforcement practices. The study employs normative legal research methods, focusing on theoretical foundations of the principle of legality, established doctrines of statutory interpretation, and comparative analysis of RoL application in common law jurisdictions, particularly the United States. The findings suggest that RoL in Indonesia should only serve as a last resort, applied strictly when all existing interpretative methods still leave unresolved ambiguity. This ensures that RoL does not undermine legal predictability while simultaneously upholding fairness in criminal adjudication. The conclusion highlights the necessity of explicitly regulating RoL within Indonesian positive law. Such regulation would provide judges with clearer guidance, reinforce protections for defendants, and contribute to achieving a balanced criminal justice system. Ultimately, the integration of RoL offers a pathway for Indonesia to harmonize its civil law tradition with a principle that enhances justice and prevents potential abuse of prosecutorial and judicial discretion.